Psychological Challenges Faced by Young Workers in the Digital Era: A Systematic Literature Review in the Indonesian Context - Sitinjak, Charli; Donatrin, Yodi; Kristiyani , Veronica; Ober, Józef (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
The digital transformation of the modern workplace has reshaped the psychological landscape for young workers, especially Millennials and Generation Z, navigating Indonesia's evolving labour market. This study presents a systematic review of empirical literature examining the psychological challenges faced by young Indonesian workers in the digital era, focussing on core themes such as burnout, stress, quiet quitting, motivation, work-life balance, and coping strategies. Guided by the PRISMA 2020 protocol, 28 peer-reviewed studies published between 2020 and 2025 were selected from the Scopus, PubMed, Google Scholar and Garuda databases. The review identifies prevalent issues such as emotional exhaustion, job insecurity, and disengagement, while also highlighting adaptive responses including intrinsic motivation, digital self-efficacy, and culturally grounded coping mechanisms. The findings underscore the importance of supportive workplace environments, leadership quality, and digital competence in mitigating psychological distress. This review not only synthesises context-specific insights, but also provides a foundation for the development of targeted interventions and policy recommendations to improve mental well-being among Indonesia’s emerging digital workforce.